Factors Relating To The Nutritional Status Of School-Age Children In Primary School Negeri 2 Bengkulu City - Anggraini, Nindia; Rohani, Tuti; Fauzi, Yusran (Journal of Multidisciplinary Research, 2025)
Background Nutritional status according to the World Health Organization (WHO) is used as a benchmark in assessing children's development and nutritional needs. Nutritional status itself can be defined as a health condition that arises from a balance between nutritional needs and the nutritional intake received by children. Based on Riskesdas (2020), the prevalence of BMI/U nutritional status at primary school age in Bengkulu Province was recorded at 2.2% of children in the very thin category, 5.2% of children were thin, 71.3% of children had normal nutritional status, 10.9% of children were obese and, 10.4% of children are obese. The aim of the research was to determine the factors related to the nutritional status of elementary school age children at SD Negeri 2 Bengkulu City. This research method is descriptive quantitative research with a cross sectional approach. The sample in this research was 80 people, taken using non-probability sampling. Data analysis was carried out using the chi-square test with a significance level of 95%. The results of the research, statistical test results show that there is a significant relationship between snack habits and nutritional status (p=0.000), show there is a significant relationship between breakfast habits and nutritional status (p=0.021), show there is no significant relationship between physical activity and nutritional status. nutrition (p=0.0990). It is hoped that schools can provide information about good nutrition to students at SDN 2 Bengkulu City .